(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2022)
This article recovers aspects of a research carried out from the National Pedagogical University (Argentina) about the teaching of contemporary agenda topics -such as recent history and the construction of memory- and the use of digital media. Based on a collaborative project, researchers and teachers analyse an interactive documentary produced by Huella Digital and the UNGS that recreates the El Campito clandestine detention center. Then we invite teachers, Initial Teacher Training and High School students to explore it. We aim to investigate which representations about state terrorism are developed by the students in different classroom scenarios using digital objects. First, we explore what the documentary provokes from a sensible level linking empathy as a gateway to social sciences subjects. Also, we analyse what this production allows due to its design, the way it organizes the information provided by it and its impact in the context of a classroom setting. Finally, we inquire about the interpretations generated from the representations suggested in the documentary.